IMPLEMENTASI LAYANAN KONSELING ISLAMI DI SEKOLAH MENENGAH ATASNEGERI 1 TANJUNG TIRAM KABUPATEN BATU BARA - Khairia Agustina (Jurnal Al-Fatih, 2019)
This research is generally aimed to describe Implementation of Islamic Counseling Service at Senior high school (SMA) Negeri 1 Tanjung Tiram. Specifically, however, this study aims to describe the implementation of counseling services Islami individual and group counseling guidance at State Senior High School 1 Tanjung Tiram, with details to describe what issues are addressed through individual and group Islamic counseling services, to describe how to carry out individual Islamic counseling services and group counseling services and any barriers that occur in carrying out individual Islamic counseling services and group counseling services. The type of research used in this thesis uses qualitative research and the approach is done using naturalistic method. The informants in this research are Headmaster, Senior high school (SMA) Negeri 1 Tanjung Tiram Batubara regency, three teacher counseling guidance (counselor) studentsof class X, XI, and XII, and the Guardian Class X, XI, and XII. Data obtained from two sources are primary data sources and secondary data sources. With data collection techniques through observation, interviews and documentation, as for data analysis techniques performed by datareducation (data collection), presentation of data, and conclusions. To ensure the validity of the data, the researcher uses triangulation technique, triangulation is definedasa data aggregation technique, that combines from various data collection technique, and data sources that already exist.